POLA ASUH ORANG TUA DALAM KEGIATAN BINA KELUARGA PADA PROSES TUMBUH DAN KEMBANG ANAK DI ERA DIGITAL - Erlina Laily Nur Afifa; Muh Faiq Abdala Diyaulhaq; Rini Sri Mulyani; Nasrul Amal; Nurhalisa, Siti (JIPD (Jurnal Inovasi Pendidikan Dasar), 2023)
This study aims to provide counseling to every parent in caring for each of their children, by using good parenting patterns through child family development activities in the digital era. This study uses qualitative research methods that are literary in nature, including the type of library research, namely research in which data collection is carried out by collecting data from various literature. Data collection was done by way of interviews and observation. Data were analyzed by means of data reduction, data presentation, and drawing conclusions. Based on the results of the analysis, there are several parenting styles consisting of authoritarian, permissive, uninvolved, authoritative, and democratic. Counseling on parenting patterns provides new insights for every parent to continue to improve their parenting style, so that they can shape the growth and development of better children in today's digital era.